Wood plastic composites weathering: Effects of compatibilization on biodegradation in soil and fungal decay. (April 2016) - Catto, André L.; Montagna, Larissa S.; Almeida, Scheyla H.; Silveira, Rosa M.B.; Santana, Ruth M.C.
Abstract: Material performance testing of wood plastic composites (WPC) requires an efficient evaluation of the resistance against biodegradation. This study investigates the effects of natural weathering on WPC and subsequent material degradation in soil and by fungi. Besides, the effectiveness of using coupling agent (CA) on adhesion of WPC and its influence in degradation was investigated. The WPC composition used was recycled polypropylene - ethylene vinyl acetate/wood flour (70/30 w/w). Four white rot fungi, Trametes villosa, Trametes versicolor, Pycnoporus sanguineus and Fuscoporia ferrea were used in a fungal decay test. For the biodegradation in simulated soil was used respirometric test. Weight loss of all materials, without and with previous natural weathering, was evaluated and surface morphology was examined by scanning electron microscopy (SEM). The results showed that natural weathering accelerated degradation process, influencing the respirometric test and fungal growth. By SEM, it was observed agglomerates of microorganisms, indicating the possible formation of biofilms. The F. ferrea fungus was more effective in surface colonization, with higher weight loss and even the emergence of reproductive structures after the incubation time. Graphical abstract: Highlights: Natural weathering influenced the biodegradation in soil and fungal attack. Wood fibers facilitated colonization of microorganisms on the surface. Fuscoporia ferrea white rot fungus was more effective, with greater weight loss. Non-weathered composites were classified as "highly resistant" and weathered composites as "resistant" to fungal attack. Pine composites showed higher biotic degradation than eucalyptus composites.